Aptamers selected for higher-affinity binding are not more specific for the target ligand - Carothers, James M. (J Am Chem Soc, 2006)
Previous study of eleven different in vitro-selected RNA aptamers that bind guanosine triphosphate (GTP) with K(d)s ranging from 8µM to 9nM showed that more information is required to specify the structures of the higher-affinity aptamers. We are interested in understanding how the more complex aptamers achieve higher affinities for the ligand. In vitro selection produces structural solutions to a functional problem that are are as simple as possible in terms of the information content needed to define them. It has long been assumed that the simplest way to improve the affinity of an aptamer is to increase the shape and functional group complementarity of the RNA binding pocket for the ligand. This argument underlies the hypothesis that selection for higher-affinity aptamers automatically leads to structures that bind more specifically to the target molecule. Here, we examined the binding specificities of the eleven GTP aptamers by carrying out competition binding studies with sixteen different chemical analogs of GTP. The aptamers have distinct patterns of specificity, implying that each RNA is a structurally-unique solution to the problem of GTP binding. However, these experiments failed to provide evidence that higher-affinity aptamers bind more specifically to GTP. We suggest that the simplest way to improve aptamer K(d)s may be to increase the stability of the RNA tertiary structure with additional intramolecular RNA-RNA interactions; increasingly-specific ligand binding may emerge only in response to direct selection for specificity.